Iowa RBA, October 13, 1997 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1997)
Iowa RBA update for October 13, 1997. Highlights of the update include the continued presence of Eurasian Collared Doves and sightings of a second year Lesser Black-backed Gull, a juvenile Sabine's Gull, Red Crossbills, and a White-faced Ibis. Also included are handwritten notes for the next week's update with sightings of Carolina Wrens, a Wilson's Phalarope and a late Cape May Warbler. Epson - sheet feed/flatbed